O Impacto Tecnológicos das Plataformas de E-commerce sobre o Comportamento do Consumidor no Brasil, de 2010 à 2020 - Pinheiro, Helena Vieira (Brasil, 2022)
Considering that human decisions and behavior are generally motivated by self-benefit, human rationality is a principle that has been present in economic theories since Adam Smith. Contemporary behavioral economics, however, deepens studies of psychology to better understand how choices are effectively made by economic agents, often mixing reason, intuition and emotion and leading to mistakes and successes. With the advent of information and communication technologies, from the civil use of the American Arpanet, there is the creation of a digital ecosystem that favors the emergence of social media and e-commerce platforms. These technologies revolutionize the exchange of information between people and companies, on a global scale and with unprecedented diversity. As this experience intensifies, characterizing the emergence of the Digital Economy, the increasing influence of social media in the search for goods and services fuels the growth of sales through e-commerce. The impact of e-commerce platforms on consumer behavior is the central theme of this work. The general objective of the study is to analyze the influence of e-commerce on sales to consumers in Brazil, while the specific objectives seek to know the products most purchased by consumers through e-commerce; identify the main types of e-commerce; raise the problems of e-commerce; and identify the best-selling product groups for men and women. The methodology is based on the use of secondary data researched from sources that publish specialized studies on the subject. Based on the dense data analyzed, it was possible to conclude that there is strong statistical evidence of the growing influence of social media, inducing consumer behavior towards a greater volume of purchases through e-commerce platforms.